Frequency, sociodemographic and clinical characteristics of adults with HIV and HBV coinfection in Peru, 2017-2021 - Hidalgo, Sebatian (2024)
Objective: To describe the frequency, sociodemographic and clinical characteristics of human immunodeficiency virus (HIV) and hepatitis B virus (HBV) coinfection. Materials and methods: A crosssectional study was conducted by cross-referencing the HIV/AIDS and HBV infection databases of the epidemiological surveillance system of Peru between 2017 and 2021. Individuals aged 18 years and older who were diagnosed with HIV and HBV coinfection were included. We collected data on variables such as age, sex, region of residence, AIDS stage, HIV transmission route, year of HIV diagnosis, year of HBV diagnosis, antiretroviral use and year of antiretroviral initiation. A bivariate analysis and a multiple correspondence analysis (MCA) were carried out. The databases of the Peruvian epidemiological surveillance system include the entire available population in that country. Results: A total of 106 adults with HIV and HBV coinfection were included. The median age at diagnosis was 32 years, and 77.88 % were between 18 and 39 years old, 87.62 % were male, and 66.02 % lived on the coast of Peru. Out of these patients, 68.57 % were diagnosed between 2018 and 2019, and 10.87 % were treated in a department other than their department of residence. In addition, 64.68 % were diagnosed with both infections in less than one year, 23.58 % were in the AIDS stage, and 44.34 % were using antiretrovirals. Conclusions: Most individuals with HIV and HBV coinfection in Peru have a median age of 32 years, live on the coast, are male, and were diagnosed in less than 12 months. MCA associations can be explained by access to the healthcare system, availability of screening tests, comprehensiveness of clinical history, and natural history of HIV.